PELATIHAN PEMROGRAMAN PROGRAMMBLELOGIC CONTROLLER GUNA MENINGKATKAN KOMPETENSIKEAHLIAN ELEKTRONIKA INDUSTRI BAGI GURU SMK - Zakaria, Masduki (Universitas Negeri Yogyakarta, 2012)
Programmable logic controller (PLC) Training programming toincrease skill competence electronics industry, is intended as an effortto contribute directly to the improvement of teacher competence vocationalcompetency skills electronics industry.The method used in this training tutorial approach and projectwork, which ended with the administration tasks. Substantially materialsprovided include sequential and combinational logic applications inPLC programming, PLC architecture, preparation of ladder diagram andstatement list, and PLC programming applications for regulating deviceinstructions of traffic lightsThe results of this activity is that participants can describe grainPLC programming competencies contained in the syllabus, and participantscan implement PLC programming instructions for regulatingtraffic lights to the setting mode 4 roads.